2010
DOI: 10.1007/s00520-010-1048-x
|View full text |Cite
|
Sign up to set email alerts
|

A pan-European survey of research in end-of-life cancer care

Abstract: BackgroundTo date, there is no coordinated strategy for end-of-life (EOL) cancer care research in Europe. The PRISMA (Reflecting the Positive Diversities of European Priorities for Research and Measurement in End-of-life Care) project is aiming to develop a programme integrating research and measurement in EOL care. This survey aimed to map and describe present EOL cancer care research in Europe and to identify priorities and barriers.Material and methodsA questionnaire of 62 questions was developed and 201 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 15 publications
(21 reference statements)
0
32
0
1
Order By: Relevance
“…Research on end-of-life cancer care, especially in Europe, has only emerged during the last two decades and still receives only minimal financial support [25]. The importance of such research is evident, as disparities between countries, within countries and among different patient populations do matter on many levels such as quality of care issues [26,27,28,29,30,31], economical aspects [32,33,34] or shifts in the delivery of care over time [35].…”
Section: Discussionmentioning
confidence: 99%
“…Research on end-of-life cancer care, especially in Europe, has only emerged during the last two decades and still receives only minimal financial support [25]. The importance of such research is evident, as disparities between countries, within countries and among different patient populations do matter on many levels such as quality of care issues [26,27,28,29,30,31], economical aspects [32,33,34] or shifts in the delivery of care over time [35].…”
Section: Discussionmentioning
confidence: 99%
“…This reflects wider research priorities 55. By restricting length of time over which differences between control and intervention are allowed to develop, any benefit inherent in the palliative approach may not be fully realised by patients in trials, hence not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although well honed in the craft of clinical governance, independent hospices may baulk at the notion of research governance, robbed as they are of NHS Research and Development (R&D) insight and support. We have surveyed independent palliative care settings in Wales and found enthusiasm for undertaking research dampened by lack of knowledge, lack of resources and concerns about financial and clinical impact—resonating with international findings elsewhere 5 9. We therefore proposed the development of guidance in the form of a research governance toolkit for independent hospices, a concept that was universally endorsed in our survey.…”
mentioning
confidence: 82%